X‐ray crystallographic and high‐speed AFM studies of peroxiredoxin 1 from Chlamydomonas reinhardtii. Issue 2 (5th February 2018) - Charoenwattanasatien, Ratana; Tanaka, Hideaki; Zinzius, Karen; Hochmal, Ana K.; Mutoh, Risa; Yamamoto, Daisuke; Hippler, Michael; Kurisu, Genji
Abstract : The oligomeric state of the 2‐Cys peroxiredoxin from the green alga Chlamydomonas reinhardtii was determined by an X‐ray crystallographic study and high‐speed AFM image analysis. Abstract : Peroxiredoxins (PRXs) are a group of antioxidant enzymes that are found in all organisms, including plants and green algae. The 2‐Cys PRX from Chlamydomonas reinhardtii ( Cr PRX1) is a chloroplast‐localized protein that is critical for clearing reactive oxygen species in chloroplasts. Cr PRX1 is reduced by thioredoxins or calredoxin ( Cr CRX), a recently identified calcium‐dependent redox protein. The molecular interaction between PRXs and thioredoxin/ Cr CRX is functionally important, but discussion has been limited owing to a lack of structural information on Cr PRX1, especially regarding its oligomeric state. In this study, high‐speed atomic force microscopy (HS‐AFM) images of Cr PRX1 and an X‐ray crystallographic analysis have enabled examination of the oligomeric state of Cr PRX1. Diffraction data from a crystal of the Cys174Ser mutant of Cr PRX1 indicate the existence of noncrystallographic fivefold symmetry. HS‐AFM images of Cr PRX1 further show that Cr PRX1 particles form rings with pentagonal rotational symmetry. On the basis of these findings, the oligomeric state of Cr PRX1 is discussed and it is concluded that this PRX exists in a ring‐shaped decameric form comprising a pentamer of dimers.